1978
DOI: 10.1099/00207713-28-4-453
|View full text |Cite
|
Sign up to set email alerts
|

Deoxyribonucleic Acid Relatedness Between Serratia plymuthica and Other Serratia Species, with a Description of Serratia odorifera sp. nov. (Type Strain: ICPB 3995)

Abstract: Seven new isolates of Serratiaplymuthica (including two from a human source) and 24 isolates resembling unclustered Serratia strain 38 (Grimont et al., J. Gen. Microbiol98:39-66, 1977) are described. Deoxyribonucleic acid relatedness studies, obtained with labeled reference deoxyribonucleic acid from s. plymuthica 392 confirm that S. plymuthica is a discrete species. Mean percent relatedness of S. plymuthica isolates to strain 392 was 88 f 13.6 (standard deviation), whereas the mean percent relatedness of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 17 publications
3
36
0
Order By: Relevance
“…As the descriptions of the Serratia species are supported by low values for DNA-DNA reassociation with their nearest neighbours (Gavini et al, 1979;Grimont et al, 1978Grimont et al, , 1979Grimont et al, , 1988, is not surprising to see most of them well separated in the phylogenetic tree. The species form two phylogenetic clusters -abbreviated Serratia clusters I and I1 (Fig.…”
Section: The Genus Serratiamentioning
confidence: 98%
See 1 more Smart Citation
“…As the descriptions of the Serratia species are supported by low values for DNA-DNA reassociation with their nearest neighbours (Gavini et al, 1979;Grimont et al, 1978Grimont et al, , 1979Grimont et al, , 1988, is not surprising to see most of them well separated in the phylogenetic tree. The species form two phylogenetic clusters -abbreviated Serratia clusters I and I1 (Fig.…”
Section: The Genus Serratiamentioning
confidence: 98%
“…Under stringent reassociation conditions, members of the three species show less than 37% relative binding (similarity), which characterizes them as genomically well-defined species (Steigerwalt et al, 1976 ;Grimont et al, 1978). Members of cluster I1 contain the other species, of which Serratia proteamaculans subsp.…”
Section: The Genus Serratiamentioning
confidence: 99%
“…S. odorifera was named in 1978 by Grimont and others, who studied 25 similar strains that were isolated mostly from various human specimens (165). S. odorifera is not pigmented and was named for its characteristic potato-like odor (165). Then, Gavini and others found that 20 organisms that had similar characteristics and that were isolated from water were a new species, and they named it S. fonticola in 1979 (145).…”
Section: Taxonomy Of Other Serratia Speciesmentioning
confidence: 99%
“…Twenty-three of the strains were isolated from human specimens, although clinical significance was not established for any of them. Two different biogroups, 1 and 2, have been identified (165). In 1985, Farmer and others described 22 S. odorifera biogroup 1 isolates and 30 biogroup 2 isolates; 16 of the biogroup 1 isolates were recovered from human specimens, and 27 of the biogroup 2 isolates were from human specimens.…”
Section: S Odoriferamentioning
confidence: 99%
See 1 more Smart Citation